Pengaruh Konflik Kerja, Stress Kerja, Beban Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan di Klinik Imam Bonjol Kota Kediri - Bella Agustina, (Jurnal Publikasi Ilmu Manajemen, 2022)
This study aims to determine and explain whether there is an influence of work conflict, work stress, workload and work motivation on employee performance at the Imam Bonjol clinic in Kediri. The sampling technique used is saturated sampling technique, with data analysis technique using validity test, reliability test, multiple linear test, classical assumption test, t test and F test. The number of samples used is 30 employees. The results of this study are that there is a partial effect of work conflict on employee performance with the value of Sig. 0.000 <0.05, which means it has a significant effect. The effect of work stress partially on employee performance with the value of Sig. 0.001 <0.05 which means it has a significant effect. Partial effect of workload on employee performance with the value of Sig. 0.015 <0.05, which means it has a significant effect and work motivation partially has an influence on employee performance with a Sig value. 0.025 <0.05 which means that work motivation has a significant effect on employee performance. On the simultaneous influence of the variables of work conflict, work stress, workload and work motivation on employee performance, the results of the value of Sig. 0.000 <0.05 which indicates that work conflict, work stress, workload and work motivation have a significant influence that can improve employee performance at the Imam Bonjol Clinic, Kediri.